Bariatric Surgery: Targeting pancreatic β cells to treat type II diabetes - Liu, Tiantong; Zou, Xi; Ruze, Rexiati; Xu, Qiang (Frontiers in Endocrinology, 2023)
Pancreatic β-cell function impairment and insulin resistance are central to the development of obesity-related type 2 diabetes mellitus (T2DM). Bariatric surgery is an effective treatment approach to treat morbid obesity and achieve lasting T2DM remission. Traditionally, sustained postsurgery glycemic control was considered a direct result of decreased nutrient intake and weight loss. However, mounting evidence in recent years implicated a weight-independent mechanism that involves pancreatic islet reconstruction and improved β-cell function. In this article, we summarize the role of β-cell in the pathogenesis of T2DM, review recent research progress focusing on the impact of Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) on pancreatic β-cell pathophysiology, and finally discuss therapeutics that have the potential to assist in the treatment effect of surgery and prevent T2D relapse.